Cultural mismatch in conversation: Spanish and Scandinavian communicative behaviour in negotiation settings - Fant, Lars (HERMES - Journal of Language and Communication in Business, 1989)
An outline of cultural differences in face-to-face behaviour between Hispanic and Nordic people is presented, and various divergences in terms of communicative priorities are proposed. The assumptions made are supported by preliminary results from research on turn-taking, back-channeling and initiative/response patterns in Spanish and Swedish negotiation dialogues, the study being based on the video-recorded corpus of the "Negotiating in Spain and Scandinavia" project carried out at three Scandinavian universities. On the basis of these results, a list of predictions is proposed concerning probabilities of misinterpretations in Hispanic-Scandinavian conversation.